Turbulent lean premixed flames - Swaminathan, Nedunchezhian; Bray, K. N. C. (Kenneth Noel Corbett), 1929- (Cambridge University Press, 2011)
"A work on turbulent premixed combustion is timely because of increased concern about the environmental impact of combustion and the search for new combustion concepts and technologies"--